Feeding Fermented Livestock from Agricultural Waste to the Bhakti Pertiwi Cattle Group, Belimbing Village, Pupuan District, Tabanan Regency - I Dewa Nyoman Sudita; Yohanes Parlindungan Situmeang (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The Provincial Government of Bali continues to encourage community farmers to form livestock groups, especially cows through the Integrated Agricultural System (“Simantri”) program since 2009/2010 which is now known as the Integrated Agricultural System (Sipadu). In addition to the program, livestock groups are also formed independently by breeders spread across Bali, one of which is the “Bhakti Pertiwi” livestock group in Belimbing Village, Pupuan-Tabanan which was only formed in 2021. Assistance in empowering its resources is the management of raising cattle and strategies for providing the animal feed. The problem faced by groups and group members is the lack of knowledge in livestock management, especially in the provision of animal feed. Farmers do not yet know which feed ingredients (grass and nuts) are good to give to livestock. As an agricultural area for rice fields and plantations, it produces a lot of agricultural waste in the form of rice straw and plantation waste in the form of coffee husks which still have potential as animal feed. Therefore, in this PKM, besides being given counseling on cattle rearing management, training is also given on the use of several types of agricultural waste as animal feed ingredients through the fermentation process. The result of this activity is that there has been a change in the behavior of group members, namely a change in knowledge about the types of feed ingredients that are good for the livestock. In changing the skills of farmers through the direct practice of how to make fermented feed, it is hoped that it can encourage farmers to utilize agricultural waste, especially rice straw as feed ingredients that can be stored. Therefore, the next group assistance activity is to monitor changes in farmers' attitudes towards the material that has been given.